2015
DOI: 10.1007/s00436-015-4723-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on oxidative stress of nitric oxide synthase interacting protein from Clonorchis sinensis

Abstract: Numerous evidences indicate that excretory-secretory products (ESPs) from liver flukes trigger the generation of free radicals that are associated with the initial pathophysiological responses in host cells. In this study, we first constructed a Clonorchis sinensis (C. sinensis, Cs)-infected BALB/c mouse model and examined relative results respectively at 3, 5, 7, and 9 weeks postinfection (p.i.). Quantitative reverse transcription (RT)-PCR indicated that the transcriptional level of both endothelial nitric ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Studies have confirmed that eNOS plays a protective role in vascular injury. It can regulate vasodilation, improve microcirculation, and reduce the occurrence of thrombus [20,21]. After examining the levels of PDCD4, Akt, and eNOS, and activation status of the Akt signaling pathway, we found that PDCD4 gene silencing activated the Akt signaling pathway and promoted the expression of eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that eNOS plays a protective role in vascular injury. It can regulate vasodilation, improve microcirculation, and reduce the occurrence of thrombus [20,21]. After examining the levels of PDCD4, Akt, and eNOS, and activation status of the Akt signaling pathway, we found that PDCD4 gene silencing activated the Akt signaling pathway and promoted the expression of eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…The amplified PCR products for wild-type and mutant TLR2 were 499 and 334 bp, respectively (Additional file 2 : Figure S1). Notably, the baseline levels of iNOS expression in the splenocytes of both mice types were remarkably higher than that in BALB/c mice [ 8 , 31 ]. The iNOS expression levels in the TLR2 wild-type and TLR2 mutant mice were remarkably induced by C. sinensis at 30 and 60 dpi, and the latter had higher iNOS expression level than the former in the corresponding period.…”
Section: Discussionmentioning
confidence: 99%
“…A study of the cancer-critical genes of C. sinensis -associated CCA showed that PSMD10 and CDK4 genes were upregulated, the tumour suppressor gene p53 and RB protein as well as BAX and caspase 9 were down-regulated, and PCNA was overexpressed in a C. sinensis- induced hamster CCA model [ 77 ]. Several researchers have proposed that oxidative stress might mediate liver fluke-associated carcinogenesis [ 78 80 ]. Serious pathological changes and increased DNA lesion products (resulting in the accumulation of lipid peroxidation products and the activation of COX-2 and 5-LOX) occurred in the hepatobiliary system of C. sinensis- infected mice, accompanied by the obvious activation of inducible NOS (iNOS) and malondialdehyde (MDA) [ 78 80 ].…”
Section: Reviewmentioning
confidence: 99%
“…Several researchers have proposed that oxidative stress might mediate liver fluke-associated carcinogenesis [ 78 80 ]. Serious pathological changes and increased DNA lesion products (resulting in the accumulation of lipid peroxidation products and the activation of COX-2 and 5-LOX) occurred in the hepatobiliary system of C. sinensis- infected mice, accompanied by the obvious activation of inducible NOS (iNOS) and malondialdehyde (MDA) [ 78 80 ]. The NOS-interacting protein of C. sinensis ( Cs NOSIP) might be a key participant in the oxidative stress observed in clonorchiasis [ 80 ].…”
Section: Reviewmentioning
confidence: 99%